Elucidating historical fisheries' networks in the Iberian Peninsula using stable isotopes. Issue 4 (18th March 2022) - Llorente‐Rodríguez, Laura; Craig, Oliver E.; Colonese, André Carlo; von Tersch, Matthew; Roselló‐Izquierdo, Eufrasia; González Gómez de Agüero, Eduardo; Fernández‐Rodríguez, Carlos; Quirós‐Castillo, Juan Antonio; López‐Arias, Begoña; Marlasca‐Martín, Ricard; Nottingham, James; Morales Muñiz, Arturo
Abstract: Processed fish is known to have been systematically traded in Europe since the Early Middle Ages to meet increasing demand of incipient markets and religious precepts, yet specific details regarding the supply of different fish in Southern Europe is often missing. Here, we address this gap through an integrated approach involving bone metrics and stable isotopic analysis of archaeological European hake ( Merluccius merluccius, Merluccidae) from the Iberian Peninsula. The results offer new insights regarding historical fisheries production systems, including the regions exploited and commercial routes, whilst also revealing biological differences between archaeological and present‐day hake populations in the North‐east Atlantic and the Mediterranean Sea. This research highlights the fruitful result of combining ichthyoarchaeological and historical data for tracking down the origin and development of historical fisheries in south‐western Europe and their bearing on modern fisheries.